Palladium Nanoparticles Encapsulated in a Silicalite-1 Zeolite Shell for Size-Selective Catalysis in Liquid-Phase Solution - Liu, C.; Liu, Jian; Yang, S.; Cao, C.; Song, W. (WILEY-V C H VERLAG GMBH, 2016)
© 2016 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim. Size-selective catalysis is of great significance in both fundamental research and industrial applications. One well-known example is zeolite-based catalysts, which show remarkable size selectivity in gas-phase reactions. However, very few of these catalysts are realized in liquid-phase solution. Herein, we report an efficient route to produce a composite composed of Pd nanoparticles encapsulated in a silicalite-1 zeolite shell. This composite shows sharp size-selective catalysis in the hydrogenation of olefin aldehydes in aqueous solution. Owing to the pore-size limitation of the silicalite-1 zeolite shell (0.53×0.56 nm), the catalyst shows high activity in the hydrogenation of 3-methyl-2-butenal (0.38×0.62 nm) and cinnamaldehyde (0.54×0.92 nm) but no activity for the hydrogenation of 3,3-diphenylacrylaldehyde (0.81×1.0 nm). A catalyst with this type of structure can be applied to load other metal nanoparticles and can serve as a useful platform to study heterogeneous size-selective catalysis in liquid solution.